Composition and rhythmic variations in the microbiome of Southwestern Atlantic corals - I. G. L. Seiblitz; K. C. C. Capel; R. R. Oliveira; C. Zilberberg; C. A. M. M. Cordeiro; C. L. B. Francini; A. A. Zanotti; A. M. Ciotti; M. V. Kitahara (Environmental Microbiome)
Abstract Background Diel and tidal rhythms can regulate the metabolism, physiology, behavior, and gene expression patterns of different organisms, with evidence of an integration on the circadian behavior of host species and their microbial community. Corals host a diverse and dynamic microbial community, with variable diversity and abundance across geographic and temporal scales. Within scleractinian corals, those that host endosymbiotic algae (i.e., zooxanthellate) display a diel variation in the oxygen levels, an oscillation in their internal environment that has the potential to influence its microbiome abundance and/or composition. Here we investigate in situ daily fluctuations on the microbial community of two zooxanthellate (Madracis decactis and Mussismilia hispida) and two azooxanthellate coral species (Tubastraea coccinea and T. tagusensis) along a 72-hour period. Results Day and night alpha diversity values were similar for all species, with Ma. decactis hosting a significantly more diverse community. Similarly, there was no fluctuation in the microbiome composition at the Amplicon Sequence Variants (ASV) level between day and night within species, but all species were significantly different from each other. Interestingly, Mu. hispida, an endemic species to the Southwestern Atlantic, had a high proportion of unidentified microbial taxa at genus level, suggesting a species-specific microbiome community composed by unidentified taxa. Significant rhythmicity in the abundance of individual ASVs was observed for one ASV (genus Pseudoalteromonas) in T. tagusensis and one (genus Woeseia) in Ma. decactis, with 24 and 12-hour fluctuations, respectively. In addition, DESeq2 recovered 13 ASVs (four in Ma. decactis, two in Mu. hispida, six in T. coccinea, and one in T. tagusensis) with different abundances between day and night. Conclusions Results show divergent microbial communities when comparing zooxanthellate and azooxanthellate species, with few significant changes within a 24-hour period. Future studies should focus on metabolic pathways to better understand how the microbiome community can adjust to environmental changes within the coral host in short time scales.